Adaptive Control and Fuzzy Control - Gaofeng, Zhou; Qi, Zhang (Modern Control Systems: Theory, Design and Applications, 2025)
The theme of this chapter focused on adaptive control and fuzzy control. Adaptive control and fuzzy control were narrated and explained separately, with related theories briefly introduced and explained. The design and analysis of controllers for adaptive control and fuzzy control were discussed. Additionally, adaptive control and fuzzy control were briefly applied to some examples, and their relative mathematical models were constructed. The design of a self-tuning regulator and an adaptive fuzzy controller was also highlighted. Furthermore, examples were provided to enhance the understanding of adaptive control and fuzzy control.